The Use of Artificial Intelligence in Sports Science to Enhance Athlete Performance - Sirawattana, Chonlakorn; Poolsamral, Chatree (Arts of Management Journal, 2024)
Artificial Intelligence (AI) in sports science is a rapidly growing trend, becoming a crucial tool for enhancing athlete performance. This academic article applies AI in various areas, such as data analysis, training strategy development, recovery processes, and strategic decision-making. AI can efficiently analyze large datasets (Big Data) related to athletes through machine learning techniques to identify trends and patterns that may not be apparent in raw data, such as movement analysis, injury patterns, and performance metrics. This information allows coaches and athletes to make informed adjustments to training strategies and competition tactics effectively. In terms of developing training strategies, AI can assist in creating personalized training programs for individual athletes by considering factors like fitness levels, physical conditions, and training goals, such as increasing strength or speed. This results in more accurate and precise models for planning training sessions. Moreover, AI plays a vital role in recovery following injuries by generating tailored rehabilitation programs and tracking recovery progress to ensure athletes return to peak performance as quickly as possible. AI also aids in strategic decision-making by analyzing data regarding opposing teams, their playing styles, strengths, and weaknesses, leading to more effective competition planning. Overall, integrating AI in sports science enhances athlete performance and contributes to the advancement of the sports industry, supporting sustainable development in the future.